Assessing spatial and temporal variation of baboon demographics in Baviaanskloof, Eastern Cape, South Africa - Mankuntsu, Elihle (Rhodes University, 2026)
Chacma baboons occur widely in southern Africa. Their flexible and opportunistic feeding behaviour allows them to easily adapt to diverse habitat conditions, readily switching their diets in response to extreme seasonal changes in food availability. They select habitats based on the availability of resources that they require, including shelter, suitable sleeping sites, food, and water. The extent to which baboons utilise different habitats has not been well explored, particularly in Baviaanskloof, where baboons are abundant. As such, in this study, I explored the spatial distribution and demographic variations of baboons across landscape types (fynbos, savanna, thicket, forest, and agricultural land). The specific objectives were to; a) scrutinise the spatial distribution of baboons across landscape types, and b) assess the demographics of baboons across landscape types. It was hypothesised that baboon spatial distribution would vary across different landscape types, and this would be based on age and sex. It was further hypothesised that adult females, juveniles, and infants would utilise forested areas more, while most baboon groups would utilise any landscape type, with more utilisation of agricultural land. To attain my objectives, camera traps were placed on a stratified random layout for two years (February 2020 to April 2022) in the Baviaanskloof area. During this time, baboons utilised agricultural land and forest more than other landscape types. As predicted, adult females, juveniles, and infants significantly used the forested area, including savanna while adult males, sub-adult males, and sub-adult females used savanna, thicket, and agricultural land more. These results suggest that baboons in Baviaanskloof use agricultural lands and landscape types such as savanna and forest, which are near water sources. This leads to higher baboon abundance and distribution in these landscapes and potentially increased human-wildlife conflict, specifically in the agricultural lands. The results may contribute to the conservation of baboons in the area since the findings indicate their distribution estimation.
Keywords: Uncatalogued